An integrated model of care to counter high incidence of HIV and sexually transmitted diseases in men who have sex with men - initial analysis of service utilizers in Zurich - Schwappach David LB; Bruggmann Philip (BMC, 2008)
Abstract Background As other countries, Switzerland experiences a high or even rising incidence of HIV and sexually transmitted infections (STI) among men who have sex with men (MSM). An outpatient clinic for gay men ("Checkpoint") was opened in 2006 in Zurich (Switzerland) in order to provide sexual health services. The clinic provides counselling, testing, medical treatment and follow-up at one location under an "open-door-policy" and with a high level of personal continuity. We describe first experiences with the new service and report the characteristics of the population that utilized it. Methods During the 6-month evaluation period, individuals who requested counselling, testing or treatment were asked to participate in a survey at their first visit prior to the consultation. The instrument includes questions regarding personal data, reasons for presenting, sexual behaviour, and risk situations. Number and results of HIV/STI tests and treatments for STI were also recorded. Results During the evaluation period, 632 consultations were conducted and 247 patients were seen by the physician. 406 HIV tests were performed (3.4% positive). 402 men completed the entry survey (64% of all consultations). The majority of respondents had 4 and more partners during the last 12 months and engaged in either receptive, insertive or both forms of anal intercourse. More than half of the responders used drugs or alcohol to get to know other men or in conjunction with sexual activity (42% infrequently, 10% frequently and 0.5% used drugs always). The main reasons for requesting testing were a prior risk situation (46.3%), followed by routine screening without a prior risk situation (24.1%) and clarification of HIV/STI status due to a new relationship (29.6%). A fifth of men that consulted the service had no history of prior tests for HIV or other STIs. Conclusion Since its first months of activity, the service achieved high levels of recognition, acceptance and demand in the MSM community. Contrary to common concepts of "testing clinics", the Checkpoint service provides post-exposure prophylaxis, HIV and STI treatment, psychological support and counselling and general medical care. It thus follows a holistic approach to health in the MSM community with the particular aim to serve as a "door opener" between the established system of care and those men that have no access to, or for any reason hesitate to utilize traditional health care.